Phylogenetic analysis of Zika and dengue virus - Muhammad Hazeeq,; T. Nataraja Moorthy,; Rasyidi Harun,; Mohd Zahedi Daud, (Malaysian Society of Applied Biology, 2016)
Zika and Dengue virus are two viruses from of the family Flaviviridae, mosquito-borne Flavivirus, known as zoonosis disease because the viruses can transmitted to human by mosquito vector mainly Aedes aegypti. The outbreaks of Zika virus (ZIKV) was first confirmed case in the Brazil in May 2015. It is currently one of the most important emerging viruses in the world and has outbreaks and epidemics with severe clinical manifestations. Like Zika, Dengue virus has rapidly spread in all areas of WHO in recent years and the source of outbreaks in areas of recent ZIKV introduction. This study aimed to determine the evolutionary relationship among Zika and Dengue virus. The 220 complete genome (11kb) were downloaded from GenBank database. Phylogenetic tree examined by constructed by Neighbor-Joining (NJ) method in the KIMURA-2 parameter model and valued by bootstrap with 1000 replicates. The result showed that Zika virus has relationship between two strains of DENV-4 where they were clustered together in phylogenetic tree.